Cough Recognition Based on Mel-Spectrogram and Convolutional Neural Network - Zhou, Quan; Shan, Jianhua; Ding, Wenlong; Wang, Chengyin; Yuan, Shi; Sun, Fuchun; Li, Haiyuan; Fang, Bin (Frontiers in Robotics and AI, 2021)
In daily life, there are a variety of complex sound sources. It is important to effectively detect certain sounds in some situations. With the outbreak of the COVID-19, it is necessary to distinguish the sound of the cough, so as to estimate suspected patients in the population. In this paper, we propose a method for cough recognition based on Mel-spectrogram and convolutional neural network called Cough Recognition Network (CRN), which can effectively distinguish the cough sounds.